Structural, Dielectric and Electrical Characteristic of Bi0.5Pb0.5[Fe0.1La0.4(Zr0.25Ti0.25)]O3 - Panda, Niranjan; Pattanayak, Samita; Choudhary, R.N.P.; Kumar, Ashok (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The polycrystalline compound Bi0.5Pb0.5 [Fe0.1La0.4 (Zr0.25Ti0.25)]O3 was synthesized by substituting Pb, La, Zr and Ti ions on perovskite structured bismuth ferrite (BFO) with the help of mixed oxide solid state reaction method. The present work is to observe the effect of off-valence and iso-valence substitution on the dielectric and electric properties of bismuth ferrite (BFO). The room temperature XRD pattern of the calcinated powders of the sample reveals that the crystal structure is tetragonal with space group P4mm, while BFO has rhombohedral structure with space group R3c. The SEM of the sintered pellet of the compound indicates that the small grains are uniformly distributed over the surface. Complex impedance spectroscopy (CIS) was adopted to analyze the dielectric, impedance and conductivity behavior of the compound. The results show that the dielectric loss in the material is significantly less than that of BFO and the dielectric and ferroelectric behavior of the sample get enhanced. The complex impedance plots show the existence of non-Debye type of relaxation phenomena, which is caused by resistive and capacitive effect of the bulk and grain boundaries. The Arrhenius plot for the compound indicates that the material possesses NTCR behavior. The frequency response of ac conductivity obeys Jonschers law and UDR (universal dielectric response). [Key words: off-valence, iso-valence, CIS, non-Debye type relaxation, NTCR, UDR]